If it's not what You are looking for type in the equation solver your own equation and let us solve it.
34y+34y=69
We simplify the equation to the form, which is simple to understand
34y+34y=69
We move all terms containing y to the left and all other terms to the right.
+34y+34y=+69
We simplify left and right side of the equation.
+68y=+69
We divide both sides of the equation by 68 to get y.
y=1.01470588235
| 4x+7=2-3x | | 4x+8=34 | | -4x^3+6x^2-5x-2= | | ln(x+1)-lnx+ln(x^2)=1 | | (6x^4+5x^3-4)-(7x^2-8x+6)= | | (2y^3+4y)-(-2y^3-5y+4)= | | -3(x-1)-6=0 | | 2(4a-3)-(2a+5)=10 | | (2z^7-6z^3+8)+(8z^6+2z^3-6z)= | | 11ab+3b^2-6ab+6b^2-13= | | x^6-8x^5+7x^6-8x^5+8= | | 4x+6=-30 | | 5x+6=-109 | | 2x^3-15x-7=0 | | w^2+3w-18= | | 164-7x=38x+19 | | 13-7x=85-21x | | 3n-2=n+14 | | 5x=4x-3x+14 | | -3,2n+4,8=5 | | x+x^3=20 | | 2x-5=x+6 | | (X^2-6)=45 | | 35-2x=7x+21 | | 4-3i=x+12yi | | 7x-4y+8.04-2.7x=5y-0.8x+2 | | 3(2x-15)=4(x+1) | | 3(2x-15)=4(4x+1) | | 2x+y-x+4yi=-1+13i | | 3(2x-15)=4(4+1) | | 5x+3yi=15+i | | 15+-3i+3iy+2x+5y=0 |